China's sustainable water-energy-food nexus by 2030: Impacts of urbanization on sectoral water demand. (1st April 2020) - Niva, Venla; Cai, Jialiang; Taka, Maija; Kummu, Matti; Varis, Olli
Abstract: In the context of China's rapid and perennial urbanization, it is of profound importance to understand how to enable and accelerate progress towards achieving the country's sustainable water-energy-food nexus by 2030. In this study, a quantitative spatial scenario analysis was performed to identify the provinces that are expected to experience changes in water stress, under the competition for water between food and energy sectors. The results manifested an imbalance of water availability for meeting the demand between those two sectors. First, food sector played the leading role in the baseline water stress. Second, energy sector dominates the increases of the projected water stress index. Third, urbanization is projected to substantially affect the extent of water availability, especially in the eastern provinces. Tackling imbalanced sectoral water demand is the key to China's sustainable water-energy-food nexus, which shall require some corresponding changes in national policy-making. China needs, first, policy coherence and synergies, second, ensuring the adequacy of any follow-up procedures, and third, embracing greater participation and transparency in policy-making. Highlights: The impacts of China's urbanization on sectoral water demand were assessed. An integrated and quantitative spatial scenario analysis was performed. Food sector played the leading role in the baseline water stress. Energy sector substantially causes the increases of the projected water stress index. Tackling imbalanced sectoral water demand is the key to sustainable water-energy-food nexus.